2500y+55000=2000y+62000

Simple and best practice solution for 2500y+55000=2000y+62000 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2500y+55000=2000y+62000 equation:


Simplifying
2500y + 55000 = 2000y + 62000

Reorder the terms:
55000 + 2500y = 2000y + 62000

Reorder the terms:
55000 + 2500y = 62000 + 2000y

Solving
55000 + 2500y = 62000 + 2000y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2000y' to each side of the equation.
55000 + 2500y + -2000y = 62000 + 2000y + -2000y

Combine like terms: 2500y + -2000y = 500y
55000 + 500y = 62000 + 2000y + -2000y

Combine like terms: 2000y + -2000y = 0
55000 + 500y = 62000 + 0
55000 + 500y = 62000

Add '-55000' to each side of the equation.
55000 + -55000 + 500y = 62000 + -55000

Combine like terms: 55000 + -55000 = 0
0 + 500y = 62000 + -55000
500y = 62000 + -55000

Combine like terms: 62000 + -55000 = 7000
500y = 7000

Divide each side by '500'.
y = 14

Simplifying
y = 14

See similar equations:

| 53=8w+5 | | 8m^2+s^2=2t | | 53=8+5 | | 4t=1o-t | | 1200m+1000=1175m+1500 | | 12.50+.40e=14.75+.25c | | 0.1y=0.2x+1 | | 3.5g+2=3.25g+5 | | 19+45= | | .20p+7=.30p+5 | | 6m+200=-6m+5.00 | | .99d=.89d+10 | | k^4+5*k^3+5*k^2-5*k-6=0 | | (-3f^2+4f-3+8f^2+7f+1)= | | 7y-3=4y+12 | | 6a+42=5a-15 | | 3p+7=1 | | 3(x+1)=-x+31 | | -24=2(3x+5)+8 | | 10a-20-9a+6=0 | | 6x+y=25 | | -4x-7=-15 | | 2x-37=5(x-2) | | 5/y+1/5=9/y | | 9a-6=4a-16 | | 3x+21+x+3=18 | | 3x/5+2x/5=4.20 | | 2a+2+a+3=8 | | 36K^2-36+108k=0 | | 7x-56=6x+12 | | 2x-2=yforx | | (8x-7)(8x+7)= |

Equations solver categories